Hepatoprotective role of vitex negundo and caesalpinia sappan in thioacetamide-induced liver injury in rats / Farkaad A.Abdul Kadir - Farkaad A. , Abdul Kadir (2014)

(untitled)
Researchers focused on developing herbal therapies as pharmacological medicines to treat liver cirrhosis that is accompanied by distortion in liver functions. This study evaluated the mechanisms of the hepatoprotective activity of Vitex negundo (VN) and Caesalpinia sappan (CS) ethanolic extracts on thioacetamide (TAA)-induced liver cirrhosis in male rats. A computer-aided prediction of hepatoprotective activity was primarily performed with prediction activity spectra of substances (PASS) program. The antioxidant properties of the crude extracts of VN and CS were evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), total phenolic content (TPC) and total flavonoid content (TFC) assays. The hepatoprotective effects of the plant extracts were measured against TAA-induced liver damage in a rat model over a period of 12 weeks. Male Sprague Dawley (SD) rats were given (0.03% w/v) TAA in their drinking water with daily oral administration of 100 mg/kg and 300 mg/kg from each plant. Silymarin (SY) was used as a reference drug that was orally administered to the animals at a daily dose of 50 mg/kg. At the end of the experiment, the liver was evaluated by the body and liver weight changes, liver gross morphology as well as histopathology, and biochemical measurements of liver parameters, AP, ALT, AST, GGT, LDH, total protein, albumin, bilirubin, serum glucose and lipid profile. The degree and stages of liver fibrosis were determined by Masson‘s trichrome staining. Hepatic cytochrome P450 2E1 (CYP2E1), matrix metalloproteinase (MMP-2 and MMP-9) and tissue inhibitor of metalloproteinase (TIMP-1) were measured. Oxidative stress was measured by malondialdehyde (MDA) level. The protective activity of VN and CS extracts were evaluated through the liver level of antioxidant enzymes (SOD, CAT and GPx). Protein expression of pro-fibrogenic TGF-β1, α-SMA and proliferating iv cell nuclear antigen (PCNA) proteins in the liver were determined and confirmed by immunohistochemical study and Western blot analysis. VN and CS extracts were tested for their cytotoxicity by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium (MTT) assay, measuring LDH and caspase-3 enzymes against hepatocarcinoma cell lines (HepG2) and antioxidant activity against hydrogen peroxide (H2O2)-induced oxidative damage in embryonic normal liver cell line (WRL-68). PASS-predicted plant activity efficiently helped in selecting the promising antioxidant, hepatoprotectants and antiproliferative pharmaceuticals with high accuracy. Our findings showed that VN and CS ethanol extracts significantly reduced the impact of TAA toxicity, and they were effectively hepatoprotective as evidenced by improved liver histopathology, immunohistochemistry and biochemistry, comparable to that of SY. The mechanism of the hepatoprotective effects of VN and CS were proposed to be through neutralizing the ROS as well as attenuation of the endogenous antioxidant activities: CAT, SOD, GPx and MDA. Additionally, VN and CS treatment had normalised the expression of TGF-β1, α-SMA, PCNA, MMPs and TIMP-1 proteins. In conclusion, the results of the present study indicate that VN and CS ethanol extracts were non-toxic and safe when administered orally, these plants possessed hepatoprotective, antioxidant and antiproliferative activities probably due to the presence of negundoside, vitegnoside and sappanchalcone as explored by PASS in VN and CS plant, respectively.